SPEECH ABNORMALITY OF THE SCHIZOPHRENIC CHARACTER IN MIDDLE SCHOOL MOVIE - Ilmiatul Hasanah (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Speech abnormality is one of the effects of schizophrenia. Schizophrenia is a mental disorder caused by the imbalance of neurotransmitter levels in the brain. The brain has the most crucial role in language process, this affects the content of the message to be conveyed. Therefore, this study aimed to analyze speech abnormality of schizophrenic’s main character in Middle School movie. This study observed the types of speech abnormality of Rafe as the main character in the Middle School film. There were two objectives in this research; first, to identify the speech abnormality found in the Rafe’s utterances in the movie; second, to identify how Rafe’s utterances hindered the process of conveying information. Based on the analysis of speech abnormality, the finding revealed that Rafe experienced all types of speech bnormality. Based on Liddle's theory, these types included poverty of speech, weakening of goal, looseness, peculiar logic, peculiar sentence, peculiar word, preservation of ideas, and distractibility. This classification was based on Liddle's theory (2002). The researcher also used Carter's (2019) theory about languages influenced by the brain. The article concludes with a few suggestions to help people understand more clearly the types of schizophrenic speech abnormality.